Antioxidant Potential and Transferrin, Ceruloplasmin, and Lipid Peroxidation Levels in Women with Preeclampsia. (1st September 2003) - Aksoy, Hülya; Taysi, Seyithan; Altinkaynak, Konca; Bakan, Ebubekir; Bakan, Nuri; Kumtepe, Yakup
Abstract : Background: The aim of this study was to evaluate lipid peroxidation and antioxidant function in patients with preeclampsia and in normotensive pregnant women and to assess an association with the severity of the disease. Methods: Twenty-one patients with mild preeclampsia, 15 patients with severe preeclampsia, and 19 normotensive pregnant women were included in the study. Plasma antioxidant potential (AOP) status, ceruloplasmin (Cp) and transferrin (Trf) levels as antioxidants, and malondialdehyde (MDA) levels as an indicator of lipid peroxidation were measured. Results: Whereas the AOP and Trf levels of the severe and mild preeclampsia groups were found to be reduced, the MDA and Cp levels were increased compared with those of the normotensive pregnant group. There were statistically significant negative correlations between AOP and MDA in all groups. No differences were observed between the groups with severe and mild preeclampsia with respect to these analytes. Conclusion: Our findings suggest that lipid peroxidation may be an important factor in the pathogenesis of preeclampsia and that plasma antioxidants and oxidants are altered in preeclampsia. However, these findings may not be useful in distinguishing women with severe and mild preeclampsia.